Relationship between digital game addiction and social skills in adolescents - Aslan, Harun; Başcıllar, Mehmet; Karataş, Kasım (Journal of Dependence, 2022)
Objective: The aim of this study is to examine the relationship between digital game addiction and social skills of children between the ages of 13-17 and to determine whether digital game addiction has a significant effect in explaining the social skills that children have with their sociodemographic information. Method: In this study, the Digital Game Addiction Scale consisting of seven items was used to measure digital game addiction and The Matson Evaluation of Social Skills with Youngsters (MESSY) consisting of forty-seven items was used to measure social skills. The sample of the study consisted of 389 children aged between 13-17 years living in Yenimahalle district of Ankara. Results: All of the children were male and the mean age was 14.86±1,28 (mean ± standard deviation). In explaining the social skill levels of children, positive social and negative social skills dimensions of the social skills assessment scale were also considered. There was also a significant relationship between digital game addiction and social skills. Conclusion: There is a significant relationship between digital game addiction and negative social skills and social behaviors in children.